Contribution of agricultural policy measures to maintain grassland areas (the case of Radensko Polje Landscape Park) - Dubravka ŽGAVEC; Klemen ELER; Andrej UDOVČ; Franc BATIČ (Acta Agriculturae Slovenica)
Within this research paper, the enforcement of agricultural policy measures for farms that have their agricultural lands within the Radensko Polje Landscape Park (RPLP) were studied. The purpose of the study was to evaluate the effectiveness of the additional payment for the extensive rearing of female bovine animals (ERB) and agri-environmental measures (AE measures) in terms of maintaining extensive agricultural systems or transitions from intensive systems to sustainable ones. This is especially desirable in the protected areas that also include landscape parks. The results of the survey of farmers of RPLP showed that both the ERB and AE measures are inefficient and fail to encourage farmers to implement more extensive farming. The main reasons for the poor enforcement of claims for ERB are intensive livestock production (milk production or bovine animals fattening), and the lack of information about the possibility of claim enforcement for ERB. Regarding AE measures, the main reasons for the failure are burdensome conditions and low financial compensation. Inventories of the composition of plant species on sample grasslands showed that the conditions of the habitats are still relatively good, because a relatively large number of species of high conservation value is present.